1996
DOI: 10.1042/bj3130661
|View full text |Cite
|
Sign up to set email alerts
|

Calmidazolium leads to an increase in the cytosolic Ca2+ concentration in Dictyostelium discoideum by induction of Ca2+ release from intracellular stores and influx of extracellular Ca2+

Abstract: The Ca2+ stores of Dictyostelium discoideum amoebae take part in control of homoeostasis of the cytosolic free Ca2+ concentration ([Ca2+]i) and the cyclic-AMP-induced [Ca2+]i-signalling cascade. In order to characterize regulatory mechanisms of these stores, we incubated cells with the calmodulin antagonist calmidazolium. Measurement of permeabilized and intact cells in suspension with a Ca(2+)-sensitive electrode revealed that calmidazolium induced Ca2+ release from intracellular stores, influx of Ca2+ across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 31 publications
5
32
0
1
Order By: Relevance
“…Calmidazolium induced an increase in [Ca 2C ] i , which is in agreement with previous findings reported in other cell types and species, such as endothelial cells (Watanabe et al 1999) and hepatoma cells (Schlatterer & Schaloske 1996, Liao et al 2009). As shown in Fig.…”
Section: Absence Of Synaptotagmin 1 In Human Parathyroid Adenomassupporting
confidence: 82%
“…Calmidazolium induced an increase in [Ca 2C ] i , which is in agreement with previous findings reported in other cell types and species, such as endothelial cells (Watanabe et al 1999) and hepatoma cells (Schlatterer & Schaloske 1996, Liao et al 2009). As shown in Fig.…”
Section: Absence Of Synaptotagmin 1 In Human Parathyroid Adenomassupporting
confidence: 82%
“…This approach, however, resulted in different observations and led to some confusion. W-7, calmidazolium, trifluoperazine, chlorpromazine, and fendiline caused Ca 2ϩ release from the endoplasmic reticulum (33)(34)(35), whereas it was also reported that they directly inhibited IICR without interacting with CaM (36).…”
Section: Remains Unclear Exogenous Cam Inhibits Iicr In a Camentioning
confidence: 99%
“…We then used the model to provide a mechanistic interpretation of the results of experiments with the application of the CaM inhibitor, calmidazolium (R24571), which causes a transient surge in cytosolic free Ca 2+ concentration. 26,28 It has been shown that one of the targets for the R24571 action is the CaM that regulates PMCA. 55,56 PMCA pumps Ca 2+ out of the cytoplasm and compensates for the constant Ca 2+ leak through the plasma membrane.…”
Section: A New Model For Camp Oscillations In Dictyostelium Exhibits mentioning
confidence: 99%
“…22 and 23. While the above computational studies have significantly advanced our understanding of various aspects of Dictyostelium behaviour, there are a range of questions that still require further elucidation. It has been shown experimentally that the levels of intracellular Ca 2+ and cAMP in Dictyostelium are tightly interconnected [24][25][26][27] and a number of experiments involving the application of calmidazolium (R24571), a calmodulin (CaM) inhibitor, to Dictyostelium have demonstrated a dramatic impact on the light scattering oscillations 26,28 which are one of the major characteristics of aggregation. 26,29 Ca 2+ has also been shown to be directly involved in cell migration via the stretch-activated Ca 2+ channels (SAC)s. 1 Previously developed models for Dictyostelium signalling and aggregation do not allow these phenomena to be investigated, however, as they all omit one or more of the networks involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation